Patient and Provider Perspectives on 30-Day Readmissions, Preventability, and Strategies for Improving Transitions of Care for Patients with HIV at a Safety Net Hospital. (13th February 2019) - Nijhawan, Ank E.; Higashi, Robin T.; Marks, Emily G.; Tiruneh, Yordanos M.; Lee, Simon Craddock
Thirty-day hospital readmissions, a key quality metric, are common among people living with HIV. We assessed perceived causes of 30-day readmissions, factors associated with preventability, and strategies to reduce preventable readmissions and improve continuity of care for HIV-positive individuals. Patient, provider, and staff perspectives toward 30-day readmissions were evaluated in semistructured interviews (n = 86) conducted in triads (HIV-positive patient, medical provider, and case manager) recruited from an inpatient safety net hospital. Iterative analysis included both deductive and inductive themes. Key findings include the following: (1) The 30-day metric should be adjusted for safety net institutions and patients with AIDS; (2) Participants disagreed about preventability, especially regarding patient-level factors; (3) Various stakeholders proposed readmission reduction strategies that spanned the inpatient to outpatient care continuum. Based on these diverse perspectives, we outline multiple interventions, from teach-back patient education to postdischarge home visits, which could substantially decrease hospital readmissions in this underserved population.